Global climate change and above- belowground insect herbivore interactions - McKenzie, Scott W.; Hentley, William T.; Hails, Rosemary S.; Jones, T. H.; Vanbergen, Adam J.; Johnson, Scott N. (Frontiers in Plant Science, 2013)
Predicted changes to the Earth’s climate are likely to affect above–belowground interactions. Our understanding is limited, however, by past focus on two-species aboveground interactions mostly ignoring belowground influences. Despite their importance to ecosystem processes, there remains a dearth of empirical evidence showing how climate change will affect above–belowground interactions. The responses of above- and belowground organisms to climate change are likely to differ given the fundamentally different niches they inhabit. Yet there are few studies that address the biological and ecological reactions of belowground herbivores to environmental conditions in current and future climates. Even fewer studies investigate the consequences of climate change for above–belowground interactions between herbivores and other organisms; those that do provide no evidence of a directed response. This paper highlights the importance of considering the belowground fauna when making predictions on the effects of climate change on plant-mediated interspecific interactions.